2022
DOI: 10.1177/02698811221112932
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of systemic chronic inflammation in diet and sleep relationship

Abstract: Background: It is well known that systemic chronic inflammation (SCI), which can be modulated by diet, is associated with poor sleep outcomes. However, the role of SCI in diet health and sleep quality relationship has not been well established. Methods: Here, by using the UK Biobank data set, we assessed the association between markers of SCI (leukocyte, platelet, lymphocyte, neutrophil, and basophil counts; C-reactive protein levels and neutrophil to lymphocyte ratio (NLR)), habitual intake of food groups, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…[38][39][40] Diet, a leading risk factor for noncommunicable diseases, affects disease risk via modulation of various mechanisms including, but not limited to, oxidative stress, plasticity, microbiota-gut-brain axis, and, most importantly, inflammatory responses. 41,42 Negative associations between adherence to a Mediterranean style diet (MED) and food groups that are abundant in these diets, such as fruits, vegetables, oily and non-oily fish, and inflammatory markers such as platelet and leukocyte counts, neutrophil to lymphocyte ratios (NLRs), and CRP [43][44][45][46][47] levels have been observed. Intervention studies have also shown a similar pattern of results.…”
Section: Systemic Chronic Inflammation Diet and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40] Diet, a leading risk factor for noncommunicable diseases, affects disease risk via modulation of various mechanisms including, but not limited to, oxidative stress, plasticity, microbiota-gut-brain axis, and, most importantly, inflammatory responses. 41,42 Negative associations between adherence to a Mediterranean style diet (MED) and food groups that are abundant in these diets, such as fruits, vegetables, oily and non-oily fish, and inflammatory markers such as platelet and leukocyte counts, neutrophil to lymphocyte ratios (NLRs), and CRP [43][44][45][46][47] levels have been observed. Intervention studies have also shown a similar pattern of results.…”
Section: Systemic Chronic Inflammation Diet and Healthmentioning
confidence: 99%
“…48,49 Based on the evidence discussed above, inflammation may mediate the association between anti-inflammatory diets, such as the MED, and health outcomes. In fact, a recent cross-sectional study found a role for various inflammatory biomarkers in the relationship between diet and sleep quality, 45 though the role of inflammation on the relationship between diet and mental and cognitive health has not yet been examined. However, there is a considerable amount of cross-sectional evidence showing that the adherence to a MED or healthy dietary patterns, including higher intakes of fruit, vegetables, fish, and wholegrains, were associated with a reduced risk of depression (but not anxiety), age-related cognitive decline, pathological neurodegeneration, and better general mental well-being.…”
Section: Systemic Chronic Inflammation Diet and Healthmentioning
confidence: 99%
“…Metabolic syndrome (MetS) is defined as a cluster of risk factors including visceral or central obesity, glucose dysregulation, hypertension, and dyslipidaemia (1) . Alongside metabolic abnormalities, MetS is strongly associated with low-grade systemic inflammation, which is thought to play a critical role in the development of mood, stress, anxiety, and sleep disorders and/or symptomology (2)(3)(4)(5) . As such, there is a strong bidirectional relationship between MetS, with anxiety disorders (4) and major depression (6) .…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned nutrients, food groups, and dietary patterns are also known to be associated with reduced systemic chronic inflammation (SCI) biomarkers, including platelet and leukocyte counts, neutrophil-to-lymphocyte ratios (NLRs), and C-reactive protein (CRP) levels [ 7 , 8 , 9 , 10 ]. For instance, large-cohort studies in healthy adults from Italy, the UK, and the US, assessing diet using food frequency questionnaires, found that adherence to a Mediterranean dietary pattern or higher healthy dietary scores was associated with lower markers of systematic chronic inflammation [ 7 , 8 , 9 ]. Additionally, a meta-analysis of five cross-sectional studies conducted in older adults (≥64 years)) revealed significant inverse associations between adherence to a Mediterranean dietary pattern and circulating CRP [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an increasing body of research has highlighted connections between sleep patterns and SCI. For instance, previous studies have noted associations between (i) higher leukocyte counts and shorter sleep duration (<8 h/night) [ 13 ], (ii) higher levels of CRP and IL-6 and shorter sleep duration (<5 h/night) [ 14 ], and (iii) higher CRP levels, platelet counts, and NLR, and poorer sleep quality [ 8 , 15 , 16 ] was observed. Similarly, the inflammatory potential of the diet, namely the Dietary Inflammatory Index (DII ® : a literature-derived estimation that is associated with circulating inflammatory biomarkers) [ 17 ] has also been shown to be related to sleep outcomes, such that more pro-inflammatory diets were correlated with shorter and longer sleep durations and lower sleep quality [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%